A century of Portuguese fertility - Livi Bacci, Massimo (Princeton University Press, 1971)
This book treats aspects of the social and demographic history of Portugal in the last century, giving particular attention to the transition from a situation of very high fertility to the moderate pattern prevailing in recent times. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of t.
Keywords: Fertility, Human -- Portugal.; Portugal -- Population.; Fécondité humaine -- Portugal.; SOCIAL SCIENCE -- Sociology -- General.; SOCIAL SCIENCE -- Anthropology -- General.; SOCIAL SCIENCE -- Regional Studies.; Fertility, Human; Population; Portugal